"Legal exhaustion" and the crisis of human rights: Tracing legal mobilization against sexual violence and torture of Kurdish women in state custody in Turkey since the 1990s. Issue 2 (15th March 2022) - Göksel, Nisa; Morse, Jaimie
Abstract: Throughout the 1990s and 2000s, Kurdish women reported sexual violence in state custody during intense conflicts between the Turkish military and the guerrilla organization PKK. Drawing on archival research and in-depth interviews with lawyers and activists in Turkey, we trace the development of legal mobilization by human rights lawyers and activists who characterized state-led sexual violence in the Kurdish region as a war crime against women and brought cases before domestic courts and the European Court of Human Rights (ECHR). Inspired by the work of Kerem Altıparmak, we develop the concept of "legal exhaustion" to characterize the emotional and relational aspects of legal mobilization in the context of war and counterterrorism politics. Bringing together scholarship in sociolegal studies and critical approaches to human rights, we argue that legal exhaustion is productive—not just an unproductive and constraining state—prompting human rights lawyers to sustain legal mobilization in/outside courts and critique national and international laws.